CNAP specification and validation: A design methodology using LOTOS and UCM. - Yi, Zhimei. (University of Ottawa (Canada), 2000)
Over the past few years, the subject of Wireless Intelligent Network (WIN) has captured the interest of the North American telecommunications community. The objective of WIN is to integrate Intelligent Network (IN) concepts into the IS-41 architecture. The introduction of a Service Control Point (SCP) in the Interim Standard IS-41 architecture enables independent specification of services. By using the IN architecture, call processing intelligence and feature functionality is separated from network switches. Subscribers can take advantage of such IN services as call name presentation (CNAP) in a wireless environment. In the first part of the thesis, we apply a scenario analysis technique to capture the requirements of the CNAP system. The analysis includes building a design model composed of User Case Maps (UCMs) and Message Sequence Charts (MSCs). This technique helps in specifying the designed system at a high level, brings us one step closer towards the specification of CNAP in LOTOS, and contributes a method for generating test cases for further validation of the specification. In the second part of the thesis, we validate the design of the CNAP feature by constructing a LOTOS specification for it and validating the specification. The formal specification of the CNAP service is based on the structure of Network Entities (NEs) that are defined in the Network Reference Model (NRM). The specification emphasizes the establishment of call connection and processing of services in a wireless environment. It is concluded that UCMs, being an intuitive notation that can be used loosely and at several levels of detail, is appropriate for the requirement and service description in the development of standard. LOTOS, being fairly precise but being able to be used abstractly, is appropriate for prototyping and validating the call procedures and services of WIN.
Keywords: Computer Science.